PENGARUH INSENTIF FINANSIAL, INSENTIF NON FINANSIAL, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA - Mery Apsari, Ni Made; Riana, I Gede (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
This research was conducted at PT. Freight Express Indonesia Denpasar Branch. Samples are taken by 32 respondents using census method. Methods of data collection is done through observation, interviews, and questionnaires. The data collection is done by distributing questionnaires using 5-point Likert scale to measure 16 question items. The collected data were analyzed using descriptive analysis techniques and multiple linear regression. The analysis showed that financial incentives, non-financial incentives and motivation have a significant effect on job satisfaction. Companies should consider the factors that may affect job satisfaction, in this case it is suggested that the company pay attention to the financial incentives, non-financial and work motivation. It aims to improve employee job satisfaction, productivity and progress for the company.
Keywords: financial incentives, non-financial incentives, motivation and job satisfaction